Networks - The Socialization of Academics - Yvonne Kreis; Kira Nierobisch (Zeitschrift für Hochschulentwicklung, 2016)
We analyze academic institutions as a place for networking. We focus on the importance of networks for the socialization of academics and the perceived impact on academic careers. In the analysis of guided interviews, we focus on the relevance of different networks for the transmission of disciplinary microcultures and the importance of interpersonal relations for network success. Our results grant new insights into network perception and the impact they have on academic socialization. This has several implications for the development of academic networks at higher education institutions.